Mediating Effect of Mathematics Attitude on the Relationship between Technological Resources and Problem-Solving Abilities of Grade 12 Students (International Journal of Scientific Research and Management (IJSRM), 2025)
Low problem-solving abilities are a crucial issue. This study aimed to determine the mediating effect of mathematics attitude on the relationship between technological resources and problem-solving abilities. Using mediation analysis involving 500 grade 12 students selected through quota sampling, it is revealed that the interest variable significantly mediates the correlation between predictive and criterion variables, partially confirming the problem-solving theory. Consequently, the following are recommended: integrating technology in education, promoting positive mathematics attitudes, and developing metacognitive skills by reflecting on problem-solving strategies and approaches.